2005
DOI: 10.1128/jcm.43.11.5760-5767.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human Infection with an Avian H9N2 Influenza A Virus in Hong Kong in 2003

Abstract: Avian H9N2 influenza A virus has caused repeated human infections in Asia since 1998. Here we report that an H9N2 influenza virus infected a 5-year-old child in Hong Kong in 2003. To identify the possible source of the infection, the human isolate and other H9N2 influenza viruses isolated from Hong Kong poultry markets from January to October 2003 were genetically and antigenically characterized. The findings of this study show that the human H9N2 influenza virus, A/Hong Kong/2108/03, is of purely avian origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
433
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 551 publications
(438 citation statements)
references
References 19 publications
(36 reference statements)
4
433
1
Order By: Relevance
“…During the past two decades many novel AIVs infecting poultry have emerged in China, including those that cause human disease (Claas et al, 1998;Butt et al, 2005;Gao et al, 2013;Guan & Smith, 2013;Wei et al, 2013;Chen et al, 2014;Su et al, 2015;Yang et al, 2015). Interestingly, almost all of these human-infecting AIVs are prevalent in live poultry markets (LPMs) in southern China, a locality often regarded as an 'epicenter' of influenza genetic diversity and emergence (Guan & Smith, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…During the past two decades many novel AIVs infecting poultry have emerged in China, including those that cause human disease (Claas et al, 1998;Butt et al, 2005;Gao et al, 2013;Guan & Smith, 2013;Wei et al, 2013;Chen et al, 2014;Su et al, 2015;Yang et al, 2015). Interestingly, almost all of these human-infecting AIVs are prevalent in live poultry markets (LPMs) in southern China, a locality often regarded as an 'epicenter' of influenza genetic diversity and emergence (Guan & Smith, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…H9N2 influenza viruses have been widely reported to infect mammals, including pigs and humans (Abolnik et al, 2010;Butt et al, 2010;Cong et al, 2007;Sun et al, 2010;Xu et al, 2007); there is evidence that a large number of people have been infected with H9N2 viruses, in particular poultry workers (Coman et al, 2013;Jia et al, 2009;Wang et al, 2009). H9N2 virus infections in humans showed typical human flu-like symptoms, which can easily go undetected or unreported (Butt et al, 2005;Lin et al, 2000). Recent studies showed that H9N2 viruses contributed the six internal genes to the novel H7N9 and H10N8 viruses that are causing severe human infections in China (Chen et al, 2014;Gao et al, 2013;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular basis of host-range restriction and adaptation of influenza A viruses to a new host species has not exactly been determined. Previous studies revealed that mutation of the polymerase complex is necessary for adaptation to a new host and may increase replication and transcription of the adapted virus in mammalian species [5,21] .…”
Section: Discussionmentioning
confidence: 99%
“…The role of the PA protein isn't exactly clear, but numerous studies indicated that it is essential for cap snatching and viral RNA promoter recognition [1,4] . During 1999 to 2003, human cases of H9N2 virus infection have been reported in China [5] . Published surveys indicated that H9N2 viruses can infect humans and it is considered to be one of the potential public health risks [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%